DETEKSI DINI (SCREENING) KANKER RONGGA MULUT DENGAN MENGGUNAKAN TOLUIDINE BLUE 1% - Mei Syafriadi; Siti Ananda Hardita Syahputri; Agung Nugroho Puspito (Multidisciplinary Journal, 2022)
Oral cancer is the most feared impact of smoking compared to other impacts because it is considered the most threatening to a person's life. 80% of oral cancer patients are smokers. A smoker has a seven times greater chance of developing oral cancer than a non-smoker. The appearance of lesions in the oral cavity resulting from a smoking habit is leukoplakia, which is white spots or plaque on the oral mucosa that cannot be peeled off. Experts say that leukoplakia is a pre-malignant lesion in the mouth. The percentage of leukoplakia that turns malignant is 3-6%. Smokers have a six times greater risk of suffering from leukoplakia than non-smokers. According to Silverman's research, of all Leukoplakia cases, 95% of sufferers are smokers. Some literature states that the peak development of leukoplakia can occur after 4 years of tobacco use. One way to detect early malignancies in the oral cavity is to use toluidine blue. Toluidine blue is an important additional diagnostic method to help identify the biopsy site and lesion boundaries, thereby providing a correct diagnosis and early treatment. Toluidine Blue 1% can be used by health workers because it does not require special skills, can be used en masse, is cheap, can be done without requiring a special room, so it can be used during social service services at Community Health Centers and Postal Service Centers.